HUBUNGAN PENGETAHUAN INFEKSI Brucella DAN FAKTOR DEMOGRAFI PETERNAK TERHADAP PERILAKU CUCI TANGAN SETELAH KONTAK DENGAN SAPI PERAH - Risqa Novita; Rina Marina (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Brucellosis is an infectious disease transmitted from livestock,especially dairy cattle, to humans, caused by bacteria Brucella sp. Brucellosis causes undulant fever and reproductive disorders in humans with a low mortality rate. The majority of dairy farmers do not know that brucellosis can spread to humans. Washing hands is one of biosecurity steps to ensure animal and human health and to prevent brucellosis. The research aims to uncover the influence of the knowledge of brucellosis in humans, the level of education, the duration of working, the history of fever, and age on the habit of washing hands after contact with dairy cow. The number of respondents was based on proportional test, 18 workers as being selected based on an inclusion criteria. They were given closed questionnaire containing questions on the knowledge of human brucellosis, demographic data and washing hand after contact with the dairy cattle. The results show that only 33.3 % of respondents know about human brucellosis, 66.7 % of respondents do not know that brucellosis can infect human. As many as 61.1 % of the respondents did not wash their hands after contact with dairy cows. Variables of age,the duration of working in dairy farm and the history of fever have p <0.02. Conclusion: variables of age, the duration of working in dairy farm and the history of fever are associated with behavior washing hand after contact with the dairy cattle. Keywords: Human brucellosis, dairy cattle, washing hand, zoonosis